2019
DOI: 10.5897/jaerd2019.1042
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, food insecurity and household adaptation mechanisms in Amaro Ward, Southern Region of Ethiopia

Abstract: Climate change poses an increasing risk to the agricultural sector and the dynamics that underpin food security. It is one of the main driving forces of the current food insecurity problem in Ethiopia and in Amaro ward in particular. The objectives of this study were to: Examine the current household food security situation in Amaro ward of Ethiopia; identify the adaptation mechanisms deployed by residents of the ward in response to the negative effects of climate change; and ascertain the coping strategies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…The turning point is observed when the coefficient of precipitation variability is 1.88. This U-shaped relationship between variability in precipitation and the total agricultural factor productivity is consistent with the results of earlier studies (such as Mendelsohn 2014;Abidoye et al 2017b;Ademe et al 2017;Baya et al 2019). For example, Baya et al (2019) argue that, as precipitation variability increases, farming households come to understand the weather changes and start to practise adaptation measures or strategies to minimise the effects of a varying climate, although this is sometimes unintended.…”
Section: Discussion Of Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The turning point is observed when the coefficient of precipitation variability is 1.88. This U-shaped relationship between variability in precipitation and the total agricultural factor productivity is consistent with the results of earlier studies (such as Mendelsohn 2014;Abidoye et al 2017b;Ademe et al 2017;Baya et al 2019). For example, Baya et al (2019) argue that, as precipitation variability increases, farming households come to understand the weather changes and start to practise adaptation measures or strategies to minimise the effects of a varying climate, although this is sometimes unintended.…”
Section: Discussion Of Resultssupporting
confidence: 86%
“…Crop production varies strongly with variability in temperature, wind and rainfall amounts received in a given area (Baya et al 2019;Sheng & Xu 2019). This relationship depends on the crop type and the location where the particular crop is grown (Ayinde et al 2017;Rötter et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings are consistent with previous studies on the PSNP’s impact on adaptive capacity. For example, a study by [ 32 ] found that the PSNP in Ethiopia had a limited impact on enhancing adaptive capacity, particularly in terms of diversifying livelihoods and increasing access to education and health services. Another study by [ 33 ] found that the PSNP had little impact on the adaptive capacity of rural households in Ethiopia, particularly in terms of reducing their vulnerability to shocks and stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Severe food shortages forced farmers to borrow. Borrowing is detestable and reproachful in societies ( Baya et al, 2019 ). Thus, farmers suffered embarrassment and humiliation and sometimes subjected to ridicule and gossip from fellow community members.…”
Section: Discussionmentioning
confidence: 99%